PELAKSANAAN PERATURAN PEMERINTAH NOMOR 41 TAHUN 2007 TENTANG ORGANISASI PERANGKAT DAERAH Studi Kasus Kota Yogyakarta - , SUWARTO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Since the enactment of Law Number 22 of 1999 on Regional Government and has been updated with shrimp Act number 32 of 2004, the Regional Governments has the authority to determine the structure of the regional organizations themselves. However, in practice, the authority owned by the Regional Governments when drafting the organization tends to ignore the principle of efficient and effective, resulting in mark-organization (proliferation). The existence of Government Regulation Number 41 of 2007 on Organization of the regional as a substitute for Government Regulation No. 8 Year 2003 on Guidelines for the Organization of the Region raises new hope that the more obvious changes in conducting arrangement as desired in the organization of regional autonomy, which is effective and efficient. In addition, the existence of Government Regulation number 41 of 2007, is an attempt to control the "obesity" bureaucracy that occurred during this time because the rules of the organization is limited by the amount of weighting based on population, area, and the number of Provincial Budgets and regency/ city. This study aims to determine the implementation of organizational management device based on the Government Regulation number 41 of 2007 in Yogyakarta Municipality in terms of content and context of policies to answer the problems in the study of how the implementation of the Government Regulation number 41 of 2007 on Organization of the Region in the City of Yogyakarta. The methodology used is a case study with qualitative descriptive research type, while the techniques of data retrieval is done through in-depth interviews, observation, and tracking documents related to the problem. The results showed that the implementation of Government Regulation number 41 of 2007 in the City of Yogyakarta has produced four regulations, consists of Regulation number 8 of 2008 on the establishment, composition, status and main tasks of the Regional Secretariat and the Secretariat of the Regional Representatives Council. Regional Regulation number 9 of 2008 on the establishment, composition, status and main tasks of the Regional Technical Institute, Regulation number 10 of 2008 on the establishment, composition, status and main tasks of the Regional Office, and Regulation number 11 of 2008 on the establishment, composition, status, the principal tasks of Sub-District. Itâs also found in this study that the city of Yogyakarta absolutely can not implement of Government Regulation number 41 of 2007, because it does not form regional organisations that became obligatory. The initiation done by the city of Yogyakarta causes the resistance and inhibition of funds from central government, especially the field of youth and sports, but on the other hand the performance of Yogyakarta was better. Itâs seen from the presence of numerous awards received by the city of Yogyakarta in terms of public service.